Feasibility, Validity, and Responsiveness of Self‐Report and Objective Measures of Physical Activity in Patients With Chronic Pain. Issue 8 (2nd April 2019) - Stevens, Matthew L.; Lin, Chung‐Wei C.; van der Ploeg, Hidde P.; De Sousa, Maria; Castle, Jessica; Nicholas, Michael K.; Maher, Chris G.
Abstract : Background: Accurate tools for measuring physical activity are important for monitoring patients with chronic pain. However, these tools have not been properly validated in this population. Objective: To determine the suitability of two physical activity measures for use in chronic pain populations. Design: Longitudinal observational study. Setting: Pain Management and Research Centre. Participants: Sixty‐four patients presenting to the Pain Management and Research Centre with chronic pain. Methods: Participants underwent a 3‐week pain management program that included cognitive behavioral strategies, education, and multiple exercises sessions per day. Physical activity was measured by the Active Australia Survey and the Actigraph GT3X at the start and end of the program. Feasibility of the physical activity measures was assessed. Criterion validity and responsiveness between the measures was compared. Correlation of physical activity with self‐rated global rating of change (GROC) scales in health were calculated. Main Outcome Measurements: Minutes per day spent in low, moderate, and vigorous physical activity; global rating of change. Results: Fifty‐two percent (n = 33) and 78% (n = 50) of participants had valid Actigraph and Active Australia data, respectively, for both time points. For criterion validity and responsiveness correlations varied (rho = −.12‐.52). All correlations between physical activity measures and GROC were small or negligible (rho ≤ .18). Conclusion: Feasibility of the Actigraph was poor compared to the Active Australia Survey. The criterion validity and responsiveness of the Active Australia Survey to the Actigraph was inconsistent and the relationship of both these measures to clinical outcomes was poor. However, limitations due to missing data mean that further research is required. Level of Evidence: III